Efficacy and safety outcomes of dulaglutide by baseline HbA1c: A post hoc analysis of the REWIND trial. Issue 9 (30th May 2022) - Franek, Edward; Gerstein, Hertzel C.; Riddle, Matthew C.; Nicolay, Claudia; Hickey, Ana; Botros, Fady T.; Loo, Li Shen
Abstract: Aim: To assess cardiovascular, glycaemic, weight and safety outcomes of long‐term treatment with dulaglutide 1.5 mg compared with placebo in patients with a baseline HbA1c of less than 7% versus 7% or higher. Materials and Methods: Intention‐to‐treat analyses were performed on REWIND participants with a baseline HbA1c measurement, using Cox proportional hazards regression and mixed model for repeated measures. Subgroup analyses with factors for baseline HbA1c categories and their interaction with treatment group, as well as analyses within the HbA1c subgroups, were conducted. Additionally, sensitivity analyses were performed for baseline HbA1c subgroups of 6.5% or less and more than 6.5%. Results: Of the 9876 eligible participants, 3921 and 5955 had a baseline HbA1c of less than 7% and 7% or higher, respectively. Mean baseline HbA1c was 6.3% and 8.0% and the mean duration of diabetes was 9.0 and 11.6 years in the respective subgroups. The less than 7% subgroup was slightly older and less frequently insulin‐treated. There was no evidence of a differential dulaglutide treatment effect on body mass index (BMI) reduction, cardiovascular or safety outcomes of interest between the baseline HbA1c subgroups. Treatment‐by‐baseline HbA1c group interaction was significant for HbA1c change from baseline ( P < .001), with a greater reduction in the subgroup with higher baseline HbA1c values. Sensitivity analyses by baseline HbA1c subgroups of 6.5% or less and more than 6.5% showed similar results. Conclusions: The reduced incidence of cardiovascular events, and the reduction in BMI in participants treated with once‐weekly dulaglutide, were independent of the baseline HbA1c level. Conversely, participants with a higher baseline HbA1c level had greater reductions in HbA1c. Dulaglutide has a positive benefit–risk profile and can be considered in patients with comparatively well‐controlled HbA1c levels seeking optimal metabolic control and cardiovascular benefits.